Perancangan Zine Sebagai Media Kampanye Sosial Peduli Pilpres 2019 Untuk Pemilih Pemula (Generasi Z) - Lily Elserisa (AKSA: Jurnal Desain Komunikasi Visual, 2020)
The concern of novice voters in the Indonesian Presidential Elections2019 was declining due to bad political problems. This made thempolitically apathetic. Many social campaigns have tried to voice this,but have not yet had an impact because they are buried by the swiftflow of information in digital media. The campaigns also do not yethave a message and media selection strategies that are close to thenovice voters which is part of generation z. The author carries out thisdesign using the Design Thinking method from Tim Brown (2009). Inthis design, the author creates visual communication for a socialcampaign. The verbal and visual message strategies adapted fromLakoff and Johnson's metaphor theory (2003). In selecting media, theauthor considering generation z and digital theory from Stillman(2017). That theory supported by the concept of media synergy fromDjito Kasilo (2008). Those strategies are applied in e-zines andprinted zine so the message of the social campaign can be accepted bynovice voters in real and virtual spaces.